Transcriptomic analysis of cytochrome P450 genes and pathways involved in chromium toxicity in Oryza sativa - Yu, Xiao-Zhang (Ecotoxicology (London, England), 2020)
In plants, cytochrome P450 monooxygenase (CYP) plays an important role in detoxifying xenobiotic chemicals and coordinating abiotic stresses. Agilent 44 K rice microarray has been used to focus on the transcriptional profile of osCYP genes in rice seedling exposed to Cr solution containing K2CrO4 or Cr(NO3)3. Our study showed that expression profiles of 264 osCYP genes identified were tissue, dose and stimulus specific in rice seedlings. Comparative genomics analysis revealed that more differentially expressed osCYP genes were discovered in roots than in shoots under both Cr exposures. Results from Venn diagram analysis of differentially expressed osCYP genes demonstrated that there were common osCYP genes and unique osCYP genes present in different rice tissue as well as in different Cr treatments, which may control and/or regulate involvement of different CYP isoenzymes under Cr exposure individually or combinedly. KEGG analysis indicated that significant up- and down-regulated osCYP genes in rice tissues were chiefly related to "biosynthesis of secondary metabolites". However, involvements of osCYP genes mapped in the "biosynthesis of secondary metabolites" were tissue and dose specific, implying their distinctly responsive and adaptive mechanisms during Cr exposure. Overall, our findings are evident to describe and clarify their individual roles of specific osCYP genes in regulating involvement of CYP isoforms in Cr detoxification by rice seedlings